Analisis Penerapan Sistem Agribisnis terhadap Pendapatan Petani Sayuran di Kabupaten Timor Tengah Utara - Krisologus Fretis; Werenfridus Taena; Melkisedik Bukifan (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Vegetable farmers in North Central Timor Regency generally obtain income from the farming subsystem, while the added value obtained from other subsystems in the agribusiness system is not considered, so research is needed. This research aims to (1) determine the application of the agribusiness system, (2) Analyze farmers' income, and (3) analyze the added value obtained by vegetable farmers in North Central Timor Regency. This research was conducted in June 2023. The research used a survey method. Data collection was carried out through observation and interviews. The sample was determined using a purposive sampling technique by as many as 60 farmers in Oelami Village, South Bikomi District, North Central Timor Regency. Data analysis uses the Likert scale, income, and added value analysis. The research results showed that implementing the vegetable agribusiness system in North Central Timor Regency is classified as moderate (56%) and good (44%), including upstream, farming, post-harvest, and marketing subsystems. The results of the income analysis show that vegetable farmers from the farming subsystem amount to Rp. 123,222,417,-. The results of the added value analysis found that the total added value was IDR. 76,177,000,- obtained from the added value of the post-harvest subsystem of IDR 40,850,000,- and the added value of the marketing subsystem of IDR 35,327,000.- The total income of farmers from vegetable agribusiness is IDR. 199,399,417. Farmers are advised to increase the implementation of vegetable agribusiness because it increases farmer income by 38.20%.